Espaços da experiência como espaços da memória: narrativas e imagens entre os canoeiros do Rio Acaraú - Venâncio, Rubens (2009)
Areas of experience as spaces of memory: narratives and images among the boatmen of the river Acaraú is the result of a social research that focuses on the experiences of memory from a group that keeps alive a secular profession in the adversities of the socio-economic modernization. Through the life trajectories of the boatmen, I seek to understand the construction of narratives backed in memory and its relationship with the city of Sobral/CE, mainly with regard to the knowledge of canoeing on the river Acaraú and the urban transformations that have occurred in the stretch of river that runs through the city.